2020
DOI: 10.1097/sla.0000000000003877
|View full text |Cite
|
Sign up to set email alerts
|

Recent Modifications of the Nuss Procedure

Abstract: Objective: To review standardized Nuss correction of pectus excavatum and vacuum bell treatment over the last 10 years. Summary of Background Data: In 2010, we reported 21 years of the Nuss procedure in 1215 patients. Methods: Over the last 10 years, 2008-2018, we evaluated 1885 pectus excavatum patients. Surgery was indicated for well-defined objective criteria. A consistent operation was performed by 8 surgeons in 1034 patients, median 15 years, (range 6-46); 996 were primary, and 38 redo operations. Surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 33 publications
(72 reference statements)
1
9
0
1
Order By: Relevance
“…One of the most common modifications to the initially described Nuss procedure is the use of multiple bars as opposed to a single bar for correction of the defect. 8 While studies show that the multiple bar Nuss operation is safe and effective, there is limited data on how multiple bars affect rates of postoperative complications. 10,12 Cierpikowski et al described an overall increase in complications with the placement of multiple bars, although specific complications were not detailed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most common modifications to the initially described Nuss procedure is the use of multiple bars as opposed to a single bar for correction of the defect. 8 While studies show that the multiple bar Nuss operation is safe and effective, there is limited data on how multiple bars affect rates of postoperative complications. 10,12 Cierpikowski et al described an overall increase in complications with the placement of multiple bars, although specific complications were not detailed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have described the use of an SE as a widely accepted and common approach to increase visualization intraoperatively. 7,8 However, the effects of the SE on postoperative complications is not well described in the literature. Much of the current data regarding SE use is focused on intraoperative side effects, such as cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelly et al presented a large cohort of 1,215 MIRPE cases over 21 years, including interval modifications to the procedure, with an update released in 2022 ( 11 , 34 ). At the time of bar removal, good or excellent surgical outcomes were reported in 96% of patients.…”
Section: Pectus Excavatum Managementmentioning
confidence: 99%
“…Therefore, surgeons must consider the risk of serious complications during surgical treatment of severe chest deformities. In several reports, scoliosis was identified in patients with PE [ 3 , 4 ], and surgical correction could be necessary for both PE and scoliosis repair. However, because a limited number of studies have reported patients who underwent surgery for PE and scoliosis, the treatment modality and surgical management for patients with both PE and scoliosis remain unclear.…”
Section: Introductionmentioning
confidence: 99%